#TITLE_ALTERNATIVE# - (NIM 20595038), MARLINA
Cellulose acetate dense membranes have been made by varied compositions of their components followed by freeze drying at certain condition. These membranes are useful for the separation of alcohol-ether mixture especially methanol-methyl tertier buthyl ether (MTBE) by pervaporation process. The results showed that higher polymer concentration resulted in denser membrane, indicated by lower flux and larger selectivity to aqua DIM Adding formamide aimed for making pores more flexible. Higher concentration of formamide resulted in higher flux of water, the swelling degree and diffusion coefficient of the permeate were also increased. Tested for freeze drying time indicated that longer freeze drying time resulted in denser membranes. Structural analysis by infrared spectroscopy showed the absence of hydrogen bond between cellulose acetate and formamide in the membrane. The bursting strength testing showed a decrease of membrane mechanical properties after the reverse osmosis process. This could be explained by the deformation and widening pore of those membranes. The swelling degree and diffusion coefficient of methanol is greater than MTBE. The optimum pervaporation temperature was 40 oC. A composition of 25% cellulose acetate, 25% formamide and freeze drying time of 48 hours gave an optimal pervaporation result, i.e. a flux of 12.603 L/m2 h and a selectivity of 39.886.